FACTORS INFLUENCING THE SELECTION OF ACCOUNTING STUDENTS IN A CAREER AS A PUBLIC ACCOUNTANT - Tri Kusno Widi Asmoro; Anita Wijayanti; Suhendro . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2016)
AbstractThe purpose of this study is to find the influence of the factors of the career selection of the S1 student at accounting department at Batik Islamic University and the University of Sebelas Maret Surakarta.This research sample using purposive sampling. The samples are 100 respondents. The analytical method is multiple linear regression.The results of this research shown that partially only factor training of professionals who have a significant influence on career selection of students S1 accounting to be public accounting. Meanwhile the salary factor, professional recognition, work environment, social values, consideration of the labor market, and personality have no significant effect. Whereas, simultaneously concluded that the factors of salaries, professional training, professional recognition, work environment, social values, labor market considerations, and personality have a positive and significant influence on student career selection of S1 accounting to be public accounting. Keywords: Career, colleger, public accounting